Melanopsin-Driven Pupil Response and Light Exposure in Non-seasonal Major Depressive Disorder - Feigl, Beatrix; Ojha, Govinda; Hides, Leanne; Zele, Andrew J. (Frontiers in Neurology, 2018)
Background: Melanopsin-expressing intrinsically photosensitive Retinal Ganglion Cells (ipRGCs) signal non-imaging forming effects of environmental light for circadian phoentrainment, the pupil light reflex and mood regulation. In seasonal affective disorder, ipRGC dysfunction is thought to cause abberant transmission of the external illumination for photoentrainment. It is not known if patients with non-seasonal depression have abnormal melanospin mediated signalling and/or irregular environmental light exposure. Methods: Twenty-one adults who live in a sub-tropical region, including eight patients with non-seasonal depression and thirteen age-matched healthy controls were recruited. The Mini International Neuropsychiatry Interview diagnosed the presence of a major depressive disorder. Light exposure was determined using actigraphy over a two week period. The melanopsin mediated post-illumination pupil response (PIPR) and outer retinal inputs to ipRGCs (transient pupil response and maximum pupil constriction amplitude) were measured in response to 1 s, short and long wavelength light with high melanopsin excitation. Results: The mean daylight exposure as a function of clock hours and total light exposure duration (mins) to illumination levels commonly recommended for depression therapy were not significantly different between groups. Out of 84 pupil measurements (42 each in the depression and control groups), the melanopsin-mediated PIPR amplitude, transient pupil response and pupil constriction amplitude were not significantly different between groups. Conclusions: This report provides initial evidence of normal melanopsin function and environmental light exposures in patients with non-seasonal depression in a subtropical location in the southern hemisphere.